STUDI LABORATORIUM PENGARUH PENAMBAHAN POLIMER SINTESIS DAN TEPUNG SAGU TERHADAP SIFAT RHEOLOGY LUMPUR AIR ASIN SISTEM DISPERSI PADA BERBAGAI TEMPERATUR - Randy Mahaputra Ginting (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2018)
Drilling is one of the important things in the drilling process, from the start of drilling to the point of reaching the intended depth, can assist the smooth process of drilling. The potential problems that can arise one of them is the drilling mud reply (loss of circulation). One way to prevent and cope with the discovery of drilling mud is dissolved. At this time Polymers Synthesis and Sago Flour as material for dissolved system. Both materials enter into the colloidal effect. The colloid solution itself is a relatively large, relatively large dispersion system within the dispersing medium.The purpose and objective in collecting these tasks is to determine the effectiveness of Synthetic and Sago Flour Polymer materials in tackling the drilling mud stock problem. Based on the results of the research found, that A sludge system can provide most of the standard specification where the value of physical properties and rheology. While the B sludge system is inversely proportional, most of it does not meet the standard specification. It can be underlined that B system with Sago Flour as LCM is effective in handling dispersion drilling mud.